Rational application of water and wastewater management in the cardboard and paper industry according to sustainability criteria - Joanna Boguniewicz-Zabłocka (Economic and Environmental Studies (E&ES), 2016)
The problems of environment protection in the industrial sectors are becoming more and more relevant, with strict legal requirements that imply considerable investments. This encourages researchers to look for new systemic solutions and methodologies to improve efficiency of environment protection while limiting costs. Industrial water and wastewater treatment plants are specific in terms of quantity and quality of treated wastewater, applied technologies and technical solutions and specific operational regime. Thus, the decision about selecting the most appropriate type of treatment technology is not easy. Such decision should be preceded by the analysis of available options based on a set of rules arising from the sustainable development criteria that coherently consider technological, environmental, economic and social issues. The paper presents case studies of rational application of industrial water and wastewater treatment in the paper and cardboard industrial sector, on the basis of sustainable development criteria. The main purpose of this article is to identify the features of sustainable water and wastewater management systems and the main problems in this regard.
Keywords: Q25; Q53; Q56; 330; sustainable water management; industrial wastewater treatment; cardboard industry